Crime, crime control and criminology in Germany - Boers, Klaus (European journal of criminology, 2017)
This article provides an overview of the situation of crime, crime control and criminology in Germany. Official crime data, victimization studies and self-reported delinquency studies consistently indicate that crime rates have been rather low in recent years, and that the amount of crime has decreased in recent years with respect to violent as well as most non-violent offences. In contrast, increasing right-wing extremist violence and Islamist terrorism are a cause for concern. After a long decline, fear of crime has recently started to increase again for certain offences such as burglary. An increase in punitive attitudes or punishment styles cannot generally be observed, and the prison rate is comparatively low. The situation of criminology in Germany is ambivalent: on the one hand, promising research is being conducted; on the other hand, the implementation of criminology within universities has been cut back.